1990
DOI: 10.1021/np50069a013
|View full text |Cite
|
Sign up to set email alerts
|

New Natural Colchicinoids: Indications of Two Possible Catabolic Routes for the Colchicine Alkaloids

Abstract: Colchicum ritchii of Jordanian origin has yielded the three non-nitrogenous colchicinoids colchicone [1], 3-demethylcolchicone [2], and comigerone [3], as well as the amidic (-)-colchibiphenyline, which in CDClj solution exists as a mixture of isomers 4a and 4b. Ketones 1-3 may exemplify one catabolic route for the colchicine alkaloids, while (-)-colchibiphenyline [4a,4b], and the accompanying and previously known (-)-androbiphenyline [5a,5b] may exemplify another.Five Colchicum species (Liliaceae) are native … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 3 publications
0
17
0
Order By: Relevance
“…15 A small number of non-nitrogen containing colchicine derivatives, such as colchicone, have also been reported. 67 …”
Section: Introductionmentioning
confidence: 99%
“…15 A small number of non-nitrogen containing colchicine derivatives, such as colchicone, have also been reported. 67 …”
Section: Introductionmentioning
confidence: 99%
“…The addition of alkali caused no noticeable shift com pared to (-)speciosine (2) [4], indicating that the hydroxyl function in (-)-speciosine (2) should be alkylated in com parison to the related (-)-O -m ethylspeciosine (1). Additionally, the H-bonded phenolic function ob served in the IR spectrum of (-)-speciosine (2) is absent in the IR spectrum of O-methylspeciosine.…”
mentioning
confidence: 95%
“…During an extensive study of the colchicine-type alkaloids and related compounds found in species belonging to the Liliaceae family, the structures of several minor alkaloids from colchicum ritchii and colchicum decaisnei were characterized and two possible catabolic pathways for the colchicine-type alkaloids were proposed [1][2].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the frame of a systematic study on the pharmacological properties of new and known colchicinoids, we intended to investigate extensively the biological properties of the non-N-containing compounds 7-deacetamido-7-oxocolchicine (2), a metabolite of colchicine [3], and 7-deacetamido-7-oxothiocolchicine (3), the so-called colchicone and thiocolchicone, respectively (thiocolchicine 10-demethoxy-10-(methylthio)colchicine). Both compounds are readily prepared in excellent yield by oxidative deamination of N-deacetylcolchicine (4) [4] and N-deacetylthiocolchicine (5) [5], respectively, with the Rapoport reagent (4-formyl-1-methylpyridinium benzenesulfonate) [6], following the protocol developed by Banwell et al [4].…”
mentioning
confidence: 99%